How do you solve -2( - 11w + 17) + 2= - 5w + 4- 9w?

1 Answer
May 24, 2018

w = 1

Explanation:

-2(-11w + 17) + 2 = -5w + 4 -9w

First, distribute -2 to -11w and 17. You do this by multiplying the numbers in the parentheses by the number on the outside. Let's make equations for this to make it easier:

-2 * -11w = 22w because two negatives create a positive.
-2 * 17 = -34 because a negative times a positive will equal a negative.

Rewrite your equation since you have distributed:

22w - 34 + 2 = -5w + 4 -9w

Now, combine like terms. What this means is that you'll be adding similar numbers and variables.

On the left side:
-34 + 2 = -32

On the right side:
-5w - 9w = -14w because two negatives added together continue to be negative. Think about a number line.

Now, rewrite your equation again:

22w - 32 = -14w + 4

Now, get rid of the lowest value variable. This is -14w. To cancel it out, add -14w to both sides. You should now have:

36w - 32 = 4

Now, add 32 to both sides to cancel out -32. You should now have:

36w = 36

Divide by 36 to isolate for w:

w = 1

To verify that this is right, I'll be plugging in this value:

-2(-11(1) + 17) + 2 = -5(1) + 4 -9(1)
22 - 34 + 2 = -5 + 4 - 9
-10 = -14 + 4
-10 = -10